Paracoccidioidomycosis in the region of Botucatu (state of São Paulo, Brazil). Evaluation of serum thyroxine (T4) and triiodothyronine (T3) levels and of the response to thyrotropin releasing hormone (TRH) - Kiy, Yoshio [UNESP]; Machado, Jussara Marcondes [UNESP]; Mendes, Rinaldo Poncio [UNESP]; Barraviera, Benedito [UNESP]; Pereira, Paulo Camara Marques [UNESP]; Cury, Paulo Roberto [UNESP] (Springer Nature, 1988)
T4, T3 and TSH serum levels were measured in 25 patients with paracoccidioidomycosis. Thyroid T3 reserves were measured on the basis of the increase in T3 (ΔT3) 2 h after intravenous injection of 200 μg TRH, and pituitary TSH reserves were measured on the basis of TSH increase (ΔTSH) 20 min after the same injection. Twenty healthy volunteers with no history of thyroid disease were used as controls. When the two groups were compared, the following results were obtained: (a) there was no significant difference in mean T4, T3, ΔTSH between groups; (b) reduced T3 levels were detected more frequently in patients with paracoccidioidomycosis, especially among those with the acute form of the disease or with the severely disseminated chronic form. The results suggest the occurrence of a reduction in peripheral conversion of T4 to T3, but do not indicate the occurrence of hypothyroidism in any of its forms (thyroid, pituitary or hypothalamic). © 1988 Kluwer Academic Publishers.
Keywords: paracoccidioidomycosis; T3; T4; thyroid; TRH; TSH; liothyronine; protirelin; thyroxine; fungus; nonhuman; south american blastomycosis; Adolescent; Adult; Aged; Human; Male; Middle Age; Paracoccidioidomycosis; Protirelin; Thyroid Gland; Thyrotropin; Thyroxine; Triiodothyronine